Achieving rapid thiosulfate-driven denitrification (TDD) in a granular sludge system. (15th February 2021) - Qian, Jin; Bai, Linqin; Zhang, Mingkuan; Chen, Lin; Yan, Xueqian; Sun, Ran; Zhang, Meiting; Chen, Guang-Hao; Wu, Di
Highlights: NO3 − removal rate of 280 mg N/L/h via sludge granulation in TDD. The properties of the granule were thoroughly characterized Extracellular proteins were essential to maintain the granular structure Denitritation activity was considerably enhanced after granulation Sulfurinomas was dominant SOB genus to drive the high-rate N removal Abstract: Sulfur-oxidizing bacteria (SOB) can drive a high level of autotrophic denitrification (AD) activity with thiosulfate (S2 O3 2− ) as the electron donor. However, the slow growth of SOB results in a low biomass concentration in the AD reactor and unsatisfactory biological nitrogen removal (BNR). In this study, our goal was to establish a high-rate thiosulfate-driven denitrification (TDD) system via sludge granulation. Granular sludge was successfully cultivated by increasing the nitrogen loading rate stepwise in thiosulfate-oxidizing/nitrate-reducing conditions in an upflow anaerobic blanket reactor. In the mature-granular-sludge reactor, a nitrate removal rate of 280 mg N/L/h was achieved with a nitrate removal efficiency of 97.7%±1.0% at a hydraulic retention time of only 15 minutes, with no nitrite detected in the effluent. Extracellular polymeric substance (EPS) analysis indicated that the proteins in loosely bound and tightly bound EPS were responsible for maintaining the compact structure of the TDD granular sludge. The dynamics of the microbial-community shift were identified by 16S rRNA high-throughput pyrosequencing analysis. The Sulfurimonas genus was found to be enriched at 74.1% of total community and may play the most critical role in the high-rate BNR. The batch assay results reveal that no nitrite accumulation occurred during nitrate reduction because the nitrate reduction rate (75.90±0.67 mg N/g MLVSS/h) was almost equal to the nitrite reduction rate (66.06±1.28 mg N/g MLVSS/h) in the thiosulfate-driven granular sludge reactor. The results of this study provide support for the establishment of a high-rate BNR system that maintains its stability with a low sludge yield. Graphical abstract: Image, graphical abstract